Stackelberg games-based distributed algorithm of pricing and resource allocation in heterogeneous wireless networks - Yong JIANG; Shan-zhi CHEN; Bo HU (Tongxin xuebao)
To deal with resource allocation in heterogeneous wireless networks,an algorithm based on multi-leader multi-follower Stackelberg games model was proposed to satisfy optimal utility of both operators and mobile users.The mobile user’s utility function with payoff and cost was designed,and it was demonstrated that the utility function obey concave function condition after defining operator price strategy,which assured the existence of Nash equilibrium point.A distributed iterative algorithm was presented to obtain optimal strategies of mobile user’s bandwidth allocation and operator’s pricing.At last,simulation experiments acquire player’s optimal strategies and Subgame perfect Nash equilibrium.